2017
DOI: 10.1128/aac.02047-16
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Activity of Gepotidacin (GSK2140944) against Neisseria gonorrhoeae

Abstract: Gepotidacin (formerly GSK2140944) is a novel, first-in-class, triazaacenaphthylene antibacterial that inhibits bacterial DNA gyrase and topoisomerase IV via a unique mechanism and has demonstrated in vitro activity against Neisseria gonorrhoeae, including drug-resistant strains, and also targets pathogens associated with other conventional and biothreat infections. Broth microdilution was used to evaluate the MIC and minimum bactericidal concentration (MBC) activity of gepotidacin and comparators against 25 N.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
55
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 20 publications
(16 reference statements)
3
55
1
Order By: Relevance
“…Similar results were seen for K. pneumoniae. These findings are consistent with prior single-step resistance selection studies that failed to recover mutants with significant resistance 9,19 . replicates; curve shows the average OD600 values at the corresponding drug concentration.…”
Section: Exceptionally Strong Synergism Between Resistance-associatedsupporting
confidence: 90%
See 3 more Smart Citations
“…Similar results were seen for K. pneumoniae. These findings are consistent with prior single-step resistance selection studies that failed to recover mutants with significant resistance 9,19 . replicates; curve shows the average OD600 values at the corresponding drug concentration.…”
Section: Exceptionally Strong Synergism Between Resistance-associatedsupporting
confidence: 90%
“…Prior studies have demonstrated that gepotidacin selectively inhibits both bacterial DNA gyrase and topoisomerase IV by a unique mechanism 9,17 , but the exact molecular mechanisms of inhibition have not been thoroughly characterized. Therefore, we first sought to study the exact molecular interactions between gepotidacin and Escherichia coli's DNA gyrase and topoisomerase IV protein complexes, using molecular modelling (see Methods).…”
Section: Molecular Modelling With Directed Evolution Accurately Predimentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, they may target multiple nonoverlapping regions of a single bacterial protein. Currently, designing multitarget antibiotics is a major focus of the pharmaceutical industry, but until now, relatively few drugs have been demonstrated to achieve a balanced inhibition of multiple microbial targets (8)(9)(10). Due to the shortage of in-depth resistance studies, our knowledge on the tempo and mode of resistance development against multitarget antibiotics remains limited (11)(12)(13).…”
mentioning
confidence: 99%